The subchondral bone layer and glenoid implant design are relevant for primary stability in glenoid arthroplasty - Sowa, Boris; Bochenek, Martin; Braun, Steffen; Kretzer, Jan Philippe; Zeifang, Felix; Bruckner, Thomas; Walch, Gilles; Raiss, Patric (Archives of orthopaedic and trauma surgery, 2018)
Background: Clinical studies suggest that reaming of the subchondral bone layer to achieve good implant seating is a risk factor for glenoid loosening. This study aims to evaluate (1) the importance of the subchondral bone layer and (2) the influence of the design of the glenoid component. - METHODS: Different techniques for preparation of an A1 glenoid were compared: (1) preserving the subchondral bone layer; (2) removal of the subchondral bone layer; (3) implantation of a glenoid component that does not adapt to the native anatomy. Artificial glenoid bones (n = 5 each) were used with a highly standardized preparation and implantation protocol. Biomechanical testing was performed during simulated physiological shoulder motion. Using a high-resolution optical system, the micromotions between implant and bone were measured up to 10,000 motion cycles. - RESULTS: At the 10,000 cycle measuring point, significantly more micromotions were found in the subchondral layer removed group than in the subchondral layer preserved group (p = 0.0427). The number of micromotions in the nonadapted group was significantly higher than in the subchondral layer preserved group (p = 0.0003) or the subchondral layer removed group (p = 0.0207). - CONCLUSION: Conservative reaming proved important to diminish the micromotions of the glenoid component. Implantation of a glenoid component that matches with the bony underlying glenoid can help to preserve the subchondral bone layer without sacrificing proper implant seating.